EU-NATO relations: Time to thaw the "frozen conflict" - Stephanie Claudia Hofmann; Christopher Reynolds (Stiftung Wissenschaft und Politik (SWP), 2007)
The EU-NATO relationship has rightly been characterised as a 'frozen conflict'. With formal cooperation between the two organisations remaining highly restricted in scope, achieving a genuine strategic partnership has been fraught with difficulties. The seriousness of the problem is illustrated by ongoing diplomatic efforts seeking to lift Turkey's veto over the implementation of EU-NATO cooperation agreements ahead of the deployment of European Security and Defence Policy (ESDP) police missions alongside NATO military operations in Afghanistan and Kosovo. So what exactly is this 'frozen conflict' and what are the implications for the EU and NATO, both politically and 'on the ground'? Moreover, what can and should be done to move beyond the current impasse?
Keywords: 320